Foramen of Winslow hernia: a case report of a rare life-threatening situation. Issue 8 (31st August 2022) - Kharkhach, Ayoub; Police, Andrea; Mabilia, Andrea; Charre, Lionel
Abstract: Internal hernias through the foramen of Winslow are considered as rare events. A 66-year-old female patient presented to our emergency department with epigastric and right upper quadrant pain associated with abdominal distention, nausea and vomiting and signs of shock. A computed tomography scan showed bowel strangulation with distended loops identified within the lesser sac. The diagnosis was confirmed by a midline laparotomy procedure. The ileum, the caecum and the ascending colon were found to herniate into the foramen of Winslow. A right hemicolectomy with a resection of the necrotic segment was performed. The patient recovered well postoperatively and was discharged on 10th day after surgery. The diagnosis and management of this rare disease remains challenging. Cross-sectional imaging with reconstruction is considered as the diagnostic modality of choice. Moreover, right hemicolectomy is a preferred procedure in order to decrease the rate of recurrence.